Determination of iron(II) concentration by potentiometric titration of chromatometry with TICl2 reduction step without heating - Simões, Eduardo Henrique; Caramello, Everton Luís [UNESP]; Júnior, Ricardo Drozdowski [UNESP]; Barrionuevo, Sandro Moreno [UNESP] (My University, 2012)
The objective of this work was to improve the method for determining the concentration of iron in accordance with standard ISO 9507: 1990 by potentiometric titration using automated chromatometry using a combined platinum electrode as indicator of analysis endpoint, coupled with reducing step performed by titanium chloride without heating of analysis solution (> 70°C). The potentiometric titration determines the final volume by the potential difference measured with high precision electrodes and calculated by derivative method with no need for color indicators and additional human intervention for endpoint indication, increasing precision and accuracy. The elimination of heating step represents a significant gain in time to perform the determination by increasing productivity of the laboratory. The use of only one solution of potassium dichromate on both titrations involving this titrant (instead of both diluted and concentrated titrant) decreases the time for solution preparation and reduces the number of burettes needed for the method. The results show the accuracy and precision of the automated system compared to reference standards used in laboratories of ores, proving no need of to heat up the sample solution during one of the steps of the method.
Keywords: Chromatometry; Iron(II); Potentiometry; Titration